Overview of financial inclusion, regulation, and education - Naoyuki Yoshino; Peter J. Morgan (Asian Development Bank Institute (ADBI), 2016)
Financial inclusion is receiving increasing attention for its potential to contribute to economic and financial development while fostering more inclusive growth and greater income equality. Although substantial progress has been made, there is still much to achieve. East Asia, the Pacific, and South Asia combined account for 55% of the world's unbanked adults, mainly in India and the People's Republic of China. This paper surveys the experiences of advanced and emerging economies - Germany, the United Kingdom, Bangladesh, India, Indonesia, the Philippines, Sri Lanka, and Thailand - to assess factors affecting the ability of low-income households and small firms to access financial services, including financial literacy, financial education programs, and financial regulatory frameworks, and to pinpoint policies that can improve their financial access while maintaining financial stability. The study aims to take a practical, holistic approach to issues related to financial inclusion. For example, innovative methods for promoting financial access, such as mobile phone banking and microfinance, require corresponding innovations in regulatory frameworks, perimeters, and capacity. Moreover, programs in the areas of financial education and consumer protection are needed to enable households and small firms to take full advantage of improvements in financial access.
Keywords: G21; G28; I22; O16; 330; financial inclusion; banks; financial regulation; payments systems; small and medium-sized enterprises; financial education